A COMPREHENSIVE REVIEW ON THE THERAPEUTIC EFFICACY OF CURCUMIN AND ITS NANOFORMULATIONS: Bioactive role of curcumin in diseases prevention - Iffat Nayila; Sumaira Sharif; Muhammad Sarwar; Faima Atta Khan; Saima Zaheer; Aasma Iqbal (BIOTROPIA, 2025)
HIGHLIGHTS- Curcumin shows strong anti-inflammatory, antioxidant, and anticancer effects.- Nanoformulations improve curcumin’s stability, absorption, and effectiveness.- Curcumin nanoparticles may protect against cancer, heart, and brain disorders.- More clinical studies are needed to confirm curcumin’s full therapeutic potential. ABSTRACTResearchers have recently focused on the bioactive components present in natural products. Over the past two decades, curcumin, the active compound derived from the Curcuma longa plant, has been extensively investigated due to its therapeutic potential as an anti-inflammatory, antioxidant, and anticancer agent. This review article aims to present the potential and therapeutic activities of curcumin based on its medicinal significance and targeted pathways. Its antibacterial, neuroprotective, antioxidant, and anticancer properties are discussed in relation to the biological activities of curcumin. Despite the promising findings, sufficient evidence supporting the adjunctive use of C. longa and curcumin-based nanoparticles for the treatment of various inflammatory and infectious disorders is still lacking. Several nanoformulations have been developed, and their effectiveness has been demonstrated in preclinical studies; however, further validation through human clinical trials is required before their application in medicine can be established. In this context, the current review provides an overview of curcumin nanoformulations that may serve as effective alternatives for targeted therapies in the management of various human disorders. According to the reported literature, nano-gels, nanoemulsions, and nano-creams loaded with curcumin nanoparticles have been proposed for the management of several diseases. The information presented in this review has been compiled from approximately 300 preclinical and clinical research papers and review articles. Further studies should focus on optimizing the stability of nanoformulations, improving clinical translation, and enhancing the therapeutic efficacy of curcumin nanoparticles in order to evaluate their potential as candidates for novel drug development in the treatment of various diseases.